Cloning of the DNA-binding subunit of human nuclear factor kappa B: the level of its mRNA is strongly regulated by phorbol ester or tumor necrosis factor alpha. - Meyer, R (1991)
The DNA binding subunit of nuclear factor kappa B (NF-kappa B), a B-cell protein that interacts with the immunoglobulin kappa light-chain gene enhancer, has been purified from nuclei of human HL-60 cells stimulated with tumor necrosis factor alpha (TNF alpha), and internal peptide sequences were obtained. Overlapping cDNA clones were isolated and sequenced. The encoded open reading frame of about 105 kDa contained at its N-terminal half all six tryptic peptide sequences, suggesting that the 51-kDa NF-kappa B protein is processed from a 105-kDa precursor. An in vitro synthesized protein containing most of the N-terminal half of the open reading frame bound specifically to an NF-kappa B binding site. This region also showed high homology to a domain shared by the Drosophila dorsal gene and the avian and mammalian rel (proto)oncogene products. The level of the 3.8-kilobase mRNA was strongly increased after stimulation with TNF alpha or phorbol ester. Thus, both factors not only activate NF-kappa B protein, as described previously, but also induce expression of the gene encoding the DNA-binding subunit of NF-kappa B.